Suicide Simulation in Primary Care. Issue 3 (March 2021) - Dye, Candice; Surapa Raju, Sai Krishna; Dy, Abigail; Gaither, Stacy L.; Tofil, Nancy M.
Abstract : Suicide is one of the leading causes of death in the 10- to 19-year-old population. Residents rarely receive training for this patient group. Increasing the knowledge and awareness of healthcare workers in diagnosing and navigating the sensitive topic of suicide in an outpatient setting is important for patient safety. Supplemental digital content is available in the text. Abstract : Objectives: This project was developed because residents need to gain knowledge and experience in promptly recognizing patients with suicidal ideation. Our study allowed pediatric interns the opportunity to manage a simulated 16-year-old actively suicidal patient in the resident continuity clinic for a well-child visit. Methods: During their first year, each resident receives simulation training. The simulation scenario for this study involves the use of a standardized patient (SP). Sessions take place in the pediatric simulation center and are recorded for observation and review. The scenario was scripted and piloted to ensure standardization in educational intervention. Postscenario, participants have a nonjudgmental debriefing with the attending physician and the SP. An anonymous survey is completed after training. Enrollment was June 2016–September 2019, with two to three 1-hour cases monthly. Results: Seventy-one postgraduate year-1 residents participated. Sixty-one residents left the suicidal patient alone/unobserved. Fifteen participants never learned of the intent of suicide during their initial intake with the patient but believed that she was depressed. The mean time to ask about suicidal ideation, when applicable, was 8:32 minutes (standard deviation 4:10 minutes, range 2:15–24:48 minutes). Common learning themes included realistic exposure to an actively suicidal patient and simulation debriefing/direct feedback from the SP. Conclusions: Practicing this crucial but somewhat rare primary care mental health emergency for all interns was possible when structured monthly. Feedback was extremely positive, with learners' feeling more prepared postsimulation. Our simulation experience also allows supervisors to assess intern's individual abilities to communicate in a difficult patient scenario which is an important physician competency as defined by the Accreditation Council for Graduate Medical Education.